The Influence of Product Prices, Sales Promotion and Services on the Purchase Decision of Indihome Products at PT. Telkom Solo - Dicky Budi Kristianto; Adhita Maharani Dewi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Digital development requires PT Telkom to continue to transform in meeting customer needs. One of its superior products is Indihome. Indihome is a wifi product. Wifi is needed by everyone in everyday life, which used to be only a secondary need is now changing to primier, without internet humans cannot move in the era of digitalization. Seeing this, researchers made a study on the influence of price variables, products and services on purchasing decisions. As a result, all of these variables have a simultaneous and partial effect on purchasing decisions.